Unimplemented of Audit Board Recommendation: Legal Review and Asset Recovery - Bayu Sujadmiko (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Recommendations of BPK in 2019 in the form of depositing money to Lampung Province, just 70% of it has been completed. The Government Internal Supervisory Apparatus does not encourage the continuity of recommendations. This study will focus on examining law enforcement on BPK recommendations related to regional financial findings that have not been acted by regional entities, analyzing obstacles to law enforcement and analysing ideal law enforcement through recommendations.This study uses empirical juridical approach. The results show that law enforcement on BPK recommendations related to regional financial findings that have not been acted upon by regional entities. Regional entities do not follow up on BPK recommendations fully, BPK will submit the disobedience to law enforcement. Furthermore, the recommendations should have improvements to the material of sanctions norms. Hence, improving the mentality of law officers, improving a commitment, maximizing the supervisory function, evaluating and monitoring the progress of the entity.